The calculus tutoring book - Ash, Carol (Wiley - IEEE Press, 1986)
This book fills an educational void by adapting unique classroom-tested techniques that students find most congenial...that strip the shroud of mystery from an esoteric subject...that prepare students for applications of calculus in later courses.